Pengaruh CR, Financial Leverage, Profitabiliyas, dan Ukuran Perusahaan terhadap Underpricing dengan Kebijakan Dividen sebagai Pemoderasi - Yudha Tri Haryogi; Sjarief Hidajat (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze dividend policy in moderating the effect of current ratio, financial leverage, profitability, and company size on stock underpricing. The population in this study amounted to 277 companies from all companies that conducted Initial Public Offering (IPO) from 2020 to August 2024. Purposive sampling was used to select 277 companies and produce 78 companies as research samples. The data analysis technique used in this study is Moderated Regression Analysis (MRA) which is used in testing the effect of moderating variables on changes in the relationship between the independent variable and the dependent variable. Based on the tests that have been carried out, the results show that the current ratio has a negative effect on underpricing, but financial leverage, profitability, and company size partially have no effect on underpricing. Meanwhile, dividend policy as a moderating variable is only able to moderate the effect of profitability on stock underpricing while the current ratio, financial leverage, company size variables are unable to be moderated by dividend policy.